Strategi Promosi Melalui Media Sosial Pada Kinasih Resort Dan Conference Bogor - Firyal, Najla Nur; Mulyana, Mumuh; Morita, Morita (Program Vokasi dan LPPM IBI Kesatuan, 2024)
The digital era can be seen as a way of life or as a time when technology is used to carry out all functions related to sustaining life. In the digital era, all activities become easier with the latest technology. Social media today can grow and engage audiences, therefore to use it as a marketing tool is a smart move. The objectives of this review are: 1) How to implement promotions via social media at Kinasih Resort and Conference Bogor; 2) What are the obstacles when promoting via social media at Kinasih Resort and Conference Bogor; 3) How to overcome obstacles that occur when promoting via social media at Kinasih Resort and Conference Bogor. The results of this review are: 1) Kinasih Resort and Conference Bogor has implemented promotions via social media; 2) In its implementation, there are obstacles experienced by Kinasih Resort and Conference Bogor in carrying out promotions via social media including Facebook, LinkedIn, Instagram and the WhatsApp social media platform; 3) To overcome the obstacles that occur when promoting via social media at Kinasih Resort and Conference Bogor, the digital marketing team re-develops the Facebook marketing strategy, the digital marketing team continues to make offers to companies, the digital marketing team develops interesting content, and provide special offers. the digital marketing team monitors social media. Keywords: Promotion via Social Media, Kinasih Resort and Conference Bogor